Evaluation of bond strength of denture teeth bonded to heat polymerized acrylic resin denture bases - Guilherme Saavedra; Maximiliano Piero Neisser; Mário Alexandre Coelho Sinhoreti; Cristiane Machado (Universidade Estadual de Campinas, 2015)
The purpose of this study was to investigate bond strength between two commercially available plastic teeth, Vitapan (Vp) and Vivadent (Vv), and two commercially available denture base resins, Classico (C) and Triplex Hot (T), as affected by tooth surface treatment. Eight experimental groups, each consisting of 5 samples, were investigated according to the variables: tooth brand (Vv or Vp), resin brand (C or T) and treated or untreated tooth surface (S or N, respectively). For surface treatment, tooth surface was grooved with aluminum oxide particles (110µm). Bond strength was evaluated with a tensile force test device on an EMIC-DL-2000 machine, speed of 0.5 mm/min, until failure. Results were evaluated statistically with ANOVA and Tukey's test (5% significance). Obtained values were (kgf): G1: Vp/C/ S=14.21 (1.07); G2: Vp/T/S=15.68 (1.09); G3: Vp/C/N=14.63 (3.51); G4: Vp/T/N=15.93 (0.82); G5: Vv/C/S=13.67 (0.73); G6: Vv/T/ S=14.99 (1.35); G7: Vv/C/N=13.37 (1.95) and G8: Vv/T/N=15.94 (2.79). Statistically significant differences were found only between groups G7 and G8 (pd".05). The following can be concluded: (1) there were statistically significant differences among Vitapan teeth and the other groups; (2) Vivadent teeth that received surface treatment showed higher bond strength values when Triplex Hot resin was used; (3) surface treatment did not modify bond strength values.